The Conflict Between Life and Death Instinct in The Scarlet Letter by Nathaniel Hawthorne - Minderop, Albertine; Hidayat, Syarif (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This study aims to show how Hawthorne uses characterization techniques and figurative languages such as metaphor and simile to describe the mental state of Arthur Dimmesdale and Hester Prynne's characters. This study uses a qualitative method with a psychological approach. The theory used in this research is the theory of life instinct and death instinct by Sigmund Freud. This study analyzes the style of language and characterizations to reveal the characters' mental conditions and inner conflict. The results of this study show that Hawthorne uses characterization techniques and figurative language to tell the conflict between the life and death instinct in Arthur Dimmesdale and Hester Prynne. Arthur Dimmesdale represents human weakness and hypocrisy that results in feelings of regret, inner conflict, and suffering that lead to the instinct of death. At the same time, the character Hester is described as having a strong and patient nature that leads to the instinct of life. This study concludes that Hawthorne uses characterization techniques and figurative language such as metaphor and simile to show the characters, Dimmesdale and Hester. They experience inner conflicts and life and death instincts.